SOCIAL CAPITAL THEORY AND CROWDFUNDING: A COMPREHENSIVE EXPLORATION - Ab Razak Che Hussin; Ahmad Amru Mohamad Zaid (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Crowdfunding (CF) has emerged as an alternative financing avenue for Small and Medium Enterprises (SMEs), particularly in response to conventional financing challenges. However, CF success is heavily influenced by funders’ trust, motivation, and perceived social alignment with the fundraiser. This study critically examines the role of Social Capital Theory in shaping CF participation on social media platforms. Through a systematic literature review (SLR), the study synthesizes theoretical frameworks, participation models, and empirical findings from 2011 to 2023. The results reveal that social capital—encompassing structural ties, trust, reciprocity, and shared norms—plays a crucial role in fostering credible crowdfunding environments. By integrating key constructs from complementary theories such as Trust Theory, Social Identity Theory, and Theory of Planned Behavior, the paper presents a holistic view of how social dynamics enhance CF participation. This insight is particularly valuable for Malaysian SMEs aiming to improve campaign engagement and build trustworthy funding communities.